From policy rate to market rates: An empirical analysis of Finnish monetary transmission - Peter Redward; Tuomas Saarenheimo (Bank of Finland, 1996)
In this paper we analyse the empirical relevance of the mechanisms through which the Bank of Finland's actions are transmitted to the Finnish economy.We concentrate on the first stage of the monetary policy transmission mechanism; namely, the effect of the Bank's actions on domestic market interest rates and the exchange rate. The questions we analyse include: What is the impact of a change in the Bank of Finland's one month tender rate on interest rates of longer maturities and on the exchange rate?How do Finnish interest rates and the exchange rate react to turmoil in foreign money and bond markets?To what extent can recent developments in Finnish interest rates be attributed to the Bank of Finland's policies? We find that the effect of a monetary policy shock is limited to the short end of the yield curve.Changes in the Bank of Finland's tender rate seem to signal the future path of short rates for a period of 1-2 years.On the other hand, Finnish bond rates appear to follow closely circumstances in the international financial market and do not seem to react systematically to changes in the Bank of Finland's tender rate.We find that monetary policy has contributed little to the large swings in Finnish bond rates experienced over the last few years.Most of the variation in bond rates can be attributed to changes in international long rates and changes in the perceived overall credibility of the Finnish economy.
URN:NBN:fi:bof-20140807327
Keywords: 330; monetary policy transmission; VAR-models; Finland